Effect of Intracycle Motion Correction Algorithm on Image Quality and Diagnostic Performance of Computed Tomography Coronary Angiography in Patients with Suspected Coronary Artery Disease - Carrascosa, Patricia (2015)
Rationale and objectives: We sought to explore the impact of intracycle motion correction algorithms (MCA) in the interpretability and diagnostic accuracy of computed tomography coronary angiography (CTCA) performed in patients suspected of coronary artery disease (CAD) referred to invasive coronary angiography. Materials and Methods: Patients with suspected CAD referred to invasive coronary angiography previously underwent CTCA. Patients under rate-control medications were advised to withhold for the previous 24hours. The primary end point of the study was to evaluate image interpretability and diagnostic performance of MCA compared to conventional reconstructions in patients referred to invasive angiography because of suspected CAD. Results: Thirty-five patients were prospectively included in the study protocol. The mean age was 61.4±9.4years. Twenty-seven (77%) patients were men. A total of 533 coronary segments were evaluated using conventional and MCA reconstructions. MCA reconstructions were associated to higher interpretability rates (525 of 533, 98.5% vs. 515 of 533, 96.6 %; P<.001) and image quality scores (3.88±0.54 vs. 3.78±0.76; P<.0001) compared to conventional reconstructions. Although only mild, a significant difference was observed regarding the diagnostic performance between reconstruction modes, with an area under the curve of 0.90 (0.87-0.92) versus 0.89 (0.86-0.92), respectively, for MCA and conventional reconstructions (. P=.0447). Conclusions: In this pilot investigation, MCA reconstructions performed in patients with suspected CAD were associated to higher interpretability rates and image quality scores compared to conventional reconstructions, although only mild differences were observed regarding the diagnostic performance between reconstruction modes.